Gian Carlo Menotti’s The Last Savage: Opera, Science, and Relevance in Cold War American Culture - Cynthia Lisa Dretel (Transposition)
This article explores Gian Carlo Menotti’s purposeful creation of a critical flop as an ethical stance against trends in mid-century American music. Menotti enjoyed popularity until shortly before the premiere of his comedic opera The Last Savage (1963), championing an approach to music and drama accessible to the general public. This opera baited the critics by consciously defying modern aesthetics, emulating Mozart’s subtle subversion of the nobility’s authority in Le nozze di Figaro. Menotti paralleled the Faustian motif of scientific discovery at the expense of society – a theme prevalent in contemporary science plays – with the rise of post-tonal music and its inaccessibility to general audiences. The eclectic score borrowed and subverted musical conventions to introduce the audience to each period of classical music and demonstrate that the elevation of post-tonal music arose from the desire to push boundaries in science. Contextualizing this opera with the science play canon reveals that the changing portrayals of scientists and technocratic elites in Cold War American media partially led to politically biased critical reception. At the height of the Space Race, scientists and artists were cultural heroes for broad swathes of the American public, as they were vital to national goals and cultural diplomacy efforts. Menotti’s application of Mozart’s comic opera tropes to satirize the upper class – in this case, an elite category representing highly educated scientists and artists – backfired.